Comparing SARS-CoV-2 Testing in Anterior Nasal Vestibular Swabs vs. Oropharyngeal Swabs - Li, Meiyan; Wei, Ruoyan; Yang, Yaling; He, Taiwen; Shen, Yinzhong; Qi, Tangkai; Han, Tian; Song, Zhigang; Zhu, Zhaoqin; Ma, Xiaopeng; Lin, Yixiao; Yuan, Yasheng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Purpose: To investigate the sensitivity of SARS-CoV-2 testing in specimens collected from the anterior nasal vestibules of COVID-19 patients. Methods: A cross-sectional analysis was performed on 30 patients with a confirmed diagnosis of COVID-19 at the Shanghai Public Health Clinical Center from March 14, 2020 to March 21, 2020. Paired specimens were collected from both the anterior nasal vestibule and the oropharynx from all patients. All specimens were tested for SARS-CoV-2 using reverse transcription-polymerase chain reaction (RT-PCR) assays. Results: Of the 30 patients with confirmed COVID-19, 17 patients (56.7%) tested positive for SARS-CoV-2 when oropharyngeal specimens were used, while 20 patients (66.7%) tested positive when nasal swab specimens were used. There was no statistically significant difference in sensitivity between the two methods. Conclusions: Respiratory swabs collected from the nasal vestibule offer a less invasive alternative to oropharyngeal swabs for specimen collection in the detection of SARS-CoV-2 infection, and have adequate sensitivity.